Implementasi Pendekatan Saintifik Berbasis Media PPT untuk Meningkatkan Motivasi Belajar Peserta Didik pada Tema 7 Perkembangan Teknologi di SD Negeri 1 Klepu Kabupaten Temanggung - Farida Mushthofaiyyah; Ervina Eka Subekti; Kuswandari Kuswandari (Jurnal Paedagogy, 2021)
This study aims to increase students' learning motivation using PPT media through a scientific approach on theme 7 technological developments at SD Negeri 1 Klepu, Temanggung Regency. This research method uses classroom action research with the research subjects being grade 3 students for the 2020/2021 academic year. This research instrument uses observation, questionnaires, and documentation. While the data analysis technique used descriptive analysis. The results of this study indicate that there is an increase in learning motivation for Theme 7 using PPT media through a scientific approach to 3rd grade students of SDN 1 Klepu. This can be seen from the increase in the average percentage of student learning outcomes from cycle I, namely 61% and 69%. Cycle 2 has increased with the acquisition of the average percentage of students' learning motivation scores from both observation sheets and questionnaires, which is 76%. Cycle 3 experienced a significant increase as seen from the results of the average percentage of students' learning motivation scores from both observation sheets and questionnaires reaching 86% and 87%, respectively. So that the expected category is the very good category with the criteria of 86% - 100% has been achieved.